Management Information Systems in Decision Making in Elementary Schools - Latifah Aprilla, Siti; Rasyid, Syahirah; Jumarwa, Jumarwa; Arisal, Arisal (DIDAKTIKA, 2023)
This study explores the implementation of a management information system (MIS) and its role in decision-making at SD Inpres 10/73 Watang Palakka. Utilizing a qualitative descriptive approach, data were collected through observation, interviews, and documentation. The findings reveal that the school has adopted a digital-based MIS, particularly through the DAPODIK platform, which enables efficient management of student and staff data. Despite some manual processes persisting—such as attendance tracking and certain assessment procedures—the digital system significantly supports school operations. The MIS has facilitated more accurate performance evaluations, streamlined report preparation, and enhanced administrative decisions, particularly during the challenges of the COVID-19 pandemic. However, limitations such as unstable internet connectivity still hinder optimal performance. Overall, the MIS contributes positively to improving the school's operational effectiveness and supports strategic decision-making by providing timely and accessible information.